Trace elements in soil pore water: a comparison of sampling methods - Di Bonito, Marcello (2005)
This thesis examined a range of methods for sampling soil pore water to investigate the chemistry of trace elements. In particular, the study assessed whether Rhizon samplers, centrifugation, high pressure squeezing and soil suspensions in simulated pore water can be viable approaches for obtaining representative samples of equilibrated soil pore water. Results for metal solubility and speciation were interpreted in terms of both soil morphological effects on trace metal dynamics and artefacts introduced at various stages during sample preparation and handling.